Sensor Networks Physical and Social Sensing in the IoT - De, Suparna; Moessner, Klaus (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
This reprint presents a collection of original research and survey articles that tackle the practical challenges in large-scale and rapid deployment of sensors for diverse applications as well as the resulting Big Data processing. The complexity of the generated data ranges from large-scale sensor networks to smartphone-enabled citizen sensing data from social networks and personal health devices, which requires advanced data processing, mining and fusion methods. Solutions listed in this book include those that address issues of the interoperability of IoT solutions and data fragmentation through crawling, indexing and searching IoT data sources and the predictive maintenance of sensors. Social networks are also in scope, through a visualisation system for the analysis of anomalies in social graphs, detecting context-aware sociability patterns and assessing the effectiveness of fine tuning and pretrained word embedding in generating interpretable topics from short texts in social networks. Applications in scope include smart tourism, fall detection through personal health sensors and an energy management expert assistant.